Effect of addition of polymerized polymethyl methacrylate (PMMA) and zirconia particles on impact strength, surface hardness, and roughness of heat cure PMMA: An in vitro study - Rasan, Duaa; Farhan, Firas (Dental hypotheses, 2023)
Introduction: This study was designed to examine the effects of addition of the combination of polymerized polymethyl methacrylate (PMMA) and zirconia (ZrO2) particles to heat cure PMMA resin on impact strength, surface hardness, and roughness. Methods: The 70% (w/w) of polymerized PMMA powder (particle size: 0.70 µm) was mixed with 30% (w/w) of zirconia powder (ZrO2) (1 µm) to produce PMMA-ZrO2 filler. Ninety acrylic specimens created were divided into three groups containing 0% wt (Control group), 2% wt, and 4% wt, PMMA-ZrO2 filler. Ten specimens were used for impact strength, surface hardness and roughness test, blindly. Data were analyzed via one-way ANOVA and the Tukey post hoc test using R 3.6.3. Results: There was statistically significant difference among study groups regarding surface hardness and roughness (p < 0.001). Yet, nonsignificant difference was found on the subject of impact strength (p = 0.33). Post hoc test showed statistically significant difference for all pairwise comparisons as regards surface hardness and roughness (p < 0.05). Conclusion: The incorporation of PMMA-ZrO2 filler did not improve impact strength (resistance during an unexpected blows or dropping). Yet, increased surface roughness and hardness, concentration-dependently.